2022
DOI: 10.1097/qad.0000000000003211
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision support systems to guide healthcare providers on HIV testing

Abstract: Objective: To understand the impact of clinical decision support systems (CDSSs) on improving HIV testing and diagnosis.Design: An original global systematic review (PROSPERO Number: CRD42020175576) of peer-reviewed articles reporting on electronic CDSSs that generate triggers encouraging healthcare providers to perform an HIV test.Methods: Medline, Embase, Cochrane CENTRAL and CINAHL EBSCOhost were searched up to 17 November 2020 and reference lists of included articles were checked. Qualitative and quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…Such prompts may be especially helpful to prevent missed testing opportunities in cases where testing was not done right away. Previous research showed that electronic prompts may increase HIV testing, although their effect is often lost when deactivated [28]. Additionally, guideline recommendations are often not adhered to without additional efforts to increase awareness of, and agreement on such recommendations [29][30][31].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Such prompts may be especially helpful to prevent missed testing opportunities in cases where testing was not done right away. Previous research showed that electronic prompts may increase HIV testing, although their effect is often lost when deactivated [28]. Additionally, guideline recommendations are often not adhered to without additional efforts to increase awareness of, and agreement on such recommendations [29][30][31].…”
Section: Plos Onementioning
confidence: 99%
“…Kroon 25 , T.J.W. van de Laar 26;27 , F. Lauw28 , M.M. van Leeuwen 5 , K. Lettinga 29 , I. Linde 1 , D.S.E.…”
unclassified
“…The systematic review by Smit et al [5] performs an interesting attempt to put order to what has been published on these alert systems (clinical decision support systems, CDSS) and to highlight their advantages and disadvantages.…”
mentioning
confidence: 99%